The Changing Face of Metabolic Disorders: Current Trends and Future Directions - Pradipta, Rifky Octavia; Efendi, Ferry (Gaceta Médica de Caracas, 2024)
Metabolic diseases, such as obesity, diabetes mellitus, and metabolic syndrome, have emerged as significant global public health concerns. Their rising prevalence, accompanied by changing lifestyles, urbanization, and dietary regimes, requires further updates on the underlying mechanisms, epidemiology, and therapeutic interventions. This editorial aims to synthesize recent findings and trends in metabolic diseases, highlighting the contribution of genetics, environmental factors, and innovative therapeutic approaches.